Penerapan Strategi Pembelajaran Inkuiri Dalam Peningkatan Kreativitas Belajar IPS Pada Siswa Sekolah Dasar - Muhammad Deni Siregar; Dukha Yunitasari (Universitas Hamzanwadi, 2018)
This research aims to improve students' learning creativity because inquiry learning is very appropriate in helping motivate students in learning. The methods used in data collection are observation and questionnaire about student's creativity, both before and after being given treatment between experiment and control class. Data analysis is done through data description and hypothesis test of research through test. The results showed that: 1. Thitung Ttabel shows a very positive relationship between the application of inquiry strategy to increase student creativity in MI NW Kelayu Jorong; 2. Students are very active in learning, they are not shy to ask questions and respond to fellow friends about IPS learning process; 3. The learning inquiry is fun and helps students during learning process; and 4. Teachers at MI NW Kelayu Jorong strongly respond to the application of inquiry in all areas of the study being taught.